2001
DOI: 10.1677/joe.0.1710481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of a new orally active growth hormone secretagogue, SM-130686

Abstract: SM-130686, an oxindole derivative, is a novel orally active GH secretagogue (GHS) which is structurally distinct from previously reported GHSs such as MK-677, NN703 and hexarelin. SM-130686 stimulates GH release from cultured rat pituitary cells in a dose-dependent manner. Half-maximum stimulation was observed at a concentration of 6⋅3 3⋅4 nM. SM-130686-induced GH release was inhibited by a GHS antagonist, but not by a GHreleasing hormone antagonist. SM-130686 dosedependently inhibited the binding of radiolabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 30 publications
(27 reference statements)
1
34
0
1
Order By: Relevance
“…It is of interest that small molecules such as SM-130686 and MK-677 can replace a larger peptide, ghrelin, bound to its specific receptor, although small molecules are used in higher concentrations than ghrelin. In addition, we have confirmed that the binding affinities of SM-130686 to 50 other receptors, including GHRH and somatostatin receptors, are lower than that with GHS-R [24].…”
Section: Binding Activity Of Sm-130686 With Ghs-rsupporting
confidence: 63%
See 1 more Smart Citation
“…It is of interest that small molecules such as SM-130686 and MK-677 can replace a larger peptide, ghrelin, bound to its specific receptor, although small molecules are used in higher concentrations than ghrelin. In addition, we have confirmed that the binding affinities of SM-130686 to 50 other receptors, including GHRH and somatostatin receptors, are lower than that with GHS-R [24].…”
Section: Binding Activity Of Sm-130686 With Ghs-rsupporting
confidence: 63%
“…In order to study the specificity of SM-130686 action through the GHS-R, several antagonists were used concomitantly with SM-130686 in cultured primary rat pituitary cells. SM-130686-induced GH release was blocked by GHS-R antagonists ([D-Arg 1 , D-Phe 5 , D-Trp 7,9 , Leu 11 ]-substance P), but not by GHRH antagonists ([N-acetyl-Try 1 , D-Arg 2 ]-hGHRH(1-29)NH 2 ) [24]. Since the binding affinities of SM-130686 with 50 other receptors were lower than that with the GHS-R as briefly mentioned above, these data indicate that SM-130686 stimulates GH release by specifically acting on the GHS-R.…”
Section: In Vitro Effect Of Sm-130686 On Gh Releasementioning
confidence: 95%
“…In adult rats, GHRP6 also increased body weight (Svensson et al 2000) as well as other GHSR agonists, like SM-130686 administered orally (Nagamine et al 2001) and BIM-28131 administered by s.c. injection (Strassburg et al 2008). It has been recently reported that GHSR1a agonist, a pentapeptide with D-amino acids, promotes weight gain in rats, by i.p.…”
Section: Discussionmentioning
confidence: 98%
“…SM-130686 has potent activity and a good pharmacokinetic profile in rats and might be a partial agonist for GHS-R 1a [37]. Repetitive administration of SM-130686 to rats, similar to repetitive administration of GH, significantly increased the fat free mass by an amount almost equal to the gain in body weight.…”
Section: Sm-130686mentioning
confidence: 93%